2013
DOI: 10.1155/2013/239628
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Multiple Imbalanced Cancer Types Based on DNA Microarray Data Using Ensemble Classifiers

Abstract: DNA microarray technology can measure the activities of tens of thousands of genes simultaneously, which provides an efficient way to diagnose cancer at the molecular level. Although this strategy has attracted significant research attention, most studies neglect an important problem, namely, that most DNA microarray datasets are skewed, which causes traditional learning algorithms to produce inaccurate results. Some studies have considered this problem, yet they merely focus on binary-class problem. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…3, where we show a scatter plot for the training data of the yeast4 problem from KEEL imbalanced dataset repository 6 [69] (attributes mcg vs. gvh) with only a 10 % of the original instances (Fig. 3a) and with the entire dataset (Fig.…”
Section: The Lack Of Data For the Map Stage In Imbalanced Classificatmentioning
confidence: 99%
See 1 more Smart Citation
“…3, where we show a scatter plot for the training data of the yeast4 problem from KEEL imbalanced dataset repository 6 [69] (attributes mcg vs. gvh) with only a 10 % of the original instances (Fig. 3a) and with the entire dataset (Fig.…”
Section: The Lack Of Data For the Map Stage In Imbalanced Classificatmentioning
confidence: 99%
“…This case study may be due to rarity of occurrence of a given concept, or even because of some restrictions during the gathering of data for a particular class. In this sense, class imbalance is ubiquitous and prevalent in several applications such as microarray research [6], medical diagnosis [7], oil-bearing of reservoir recognition [8], or intrusion detection systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have conducted comparative studies, like the ones reported in [35,43,56]. Authors such as [63] suggest that SVM behave well in general for this problems, although it is important to consider that such method was originally developed for bi-class problems, and applying SVMs to multi-class classification implies a number of additional steps, that might not be easy to accomplish, as described in [54].…”
Section: Classifiersmentioning
confidence: 99%
“…In [63], the authors deal with multi-class imbalance classification problems. The method divides multiclass problems into multiple binary-class problems.…”
Section: Classifiersmentioning
confidence: 99%
“…Generalised Radial Basis Function neural networks were used for improving prediction accuracy in gene classification using three filter techniques for feature selection of microarray data (Fern谩ndez-Navarro et al, 2012). Yu et al (2013a) performed a feature selection in DNA microarrays using an ensemble learning technique. In addition, they used an algorithm that converts a multi-class problem into multiple binary classes to reduce the complexity of the problem.…”
Section: Introductionmentioning
confidence: 99%